Research and implementation of intelligent power supply health management scheme for super large scale complex embedded system - Lei Zhiguang; Xing Lei; Lei Zhijun (Dianzi Jishu Yingyong)
With the diversified development of embedded systems, continuous technological advancements and the increasing demand for applications, the hardware platforms of embedded systems are also showing a diversified trend. From the initial simple processors to the current multi-core processors, such as FPGAs, ASICs and so on, the hardware platforms of embedded systems have become increasingly complex. Power integrity, especially, faces severe challenges as the number of power channels in embedded systems increases, power consumption surges, power-on timing requirements become more stringent, and reset signal classification becomes more complex. Therefore, intelligent digital power health management units have become increasingly important. This paper implements 14-channel power-on sequence control, voltage monitoring, temperature monitoring, reset signal and configuration signal control based on TI's digital power on-sequence control circuit UCD9090 and digital PWM system control circuit UCD9244. Compared with traditional intelligent digital power health management solutions, this scheme offers flexible control, simple implementation, and requires no complex coding. The application of this solution in the system has shortened the product's time to market.